Experimental investigation on the melting and solidification performance enhancement of a fractal latent heat storage unit. (November 2021) - Huang, Yongping; Han, Qun; Liu, Xiangdong
Highlights: Heat charging/discharging of a fractal tree-shaped finned LHS unit is studied. Effect of inclination on thermal performance of fractal LHS units is analyzed. Horizontally positioned fractal LHS units obtains the maximum melting rate. Fractal LHS unit is less affected by orientations than the traditional one. Inclination angle affects melting process more than solidification process. Abstract: This work designs a fractal latent heat storage (LHS) unit with tree-shaped fins for enhancing heat exchange efficiency. The melting/solidification processes inside a fractal LHS unit are experimentally studied by visualization observation, focusing on the role of inclination angles. Comparative studies on fractal LHS and traditional LHS units are conducted by assessing the temperature response, phase change behavior, liquid fraction variation, and thermal storage/release performance. The experimental results indicate that the inclination angle presents a more significant impact on melting processes than solidification processes, especially for thermal characteristics in the axial direction. Variations in the onset and duration of natural convection determine the main difference in the melting/solidification mechanism of fractal LHS units. Large inclination angle is not conducive to convection development, thus prolonging the late conduction-dominated stage and diminishing the overall thermal performance. Therefore, the thermal characteristics of fractal LHS units are less affected by orientations than traditional LHS units. Moreover, the overall thermal performance of fractal LHS units is more superior to traditional LHS units irrespective of orientations. Particularly, the vertical fractal LHS unit has a maximum reduction of 52.6% in the complete melting duration, and the heat storage/release rate of horizontal fractal LHS units augments by 94.7% and 101.5% when compared with traditional LHS units.